Modelling and fabrication of inhalable microbubbles for drug targeting in the lungs - Min, H (2024)
Microbubble ultrasound contrast agents have been used safely and effectively in diagnostic applications for several decades. Although their use in the lungs has not been widely explored due to safety concerns and poor ultrasound penetration through gas-filled tissue, the fragile and low-density properties of microbubbles make them attractive for drug delivery. This thesis aims to investigate the potential of microbubbles as inhalable agents for treating lung conditions.